Mapping Physical Training Materials and Diet Management for Football Athletes - Ardi Nusri; Esi Emilia; Tyas Permatasari; Yatty Destani Sandy; Caca Pratiwi; Erni Rukmana; Latifah Rahman Nurfazriah (STKIP Muhammadiyah Kuningan, 2022)
The physical component and food intake are significant factors in football. The aims of this study were 1) to identify materials and media for physical exercise and diet management for soccer athletes and 2) to map physical training materials and diet management for soccer athletes. The method used is Research and Development (R&D) with the Four-D (4D) model. The population in this study were football athletes and coaches. The sample consisted of 82 athletes and football coaches from PSMS Medan. Data analysis using descriptive analysis. The results showed that 95% of the sample agreed that all physical training material needs to be known by football athletes. The material indicators are anatomy and physiology, components of the physical conditions required in soccer, energy systems, principles of soccer physical training, training volume and intensity, training stages, preparation stages, training stages, match stages, training stages, transitions, and recovery exercises as well as weight training. This study also showed that 95.3% of the sample required an assessment or assessment of nutritional data on soccer athletes, such as body measurements/anthropometrics, body composition measurements, and dietary and healthy history. The conclusion of the study is that diet management material that athletes and soccer coaches need to know is Sports Classification According to the Metabolic System, Assessment or Assessment of Nutritional Data on Soccer Athletes, Nutritional Problems in Soccer Athletes, Nutritional Interventions in Soccer Athletes; Monitoring and Evaluation of Nutrition in Football Athletes.